Mentalizing Glasses: Multifocal Attention in Mentalization-Based Treatment and the Role of the Supervision - Tohme, Pia; Kolev, Martin (Frontiers in Psychology, 2021)
Bifocal attention has been conceptualized differently by various scholars; however all converge in the idea that the therapeutic process includes the need for the therapist to focus his attention on more than one aspect of the therapeutic setting. We propose a novel view in the application of bifocal attention within the mentalizing framework (MBT) of working with children, adolescents and their families. We start by providing a short history of the evolution of the construct of bifocal attention, followed by a brief description of the structure of MBT for children and adolescents, emphasizing the crucial role of bifocal and multiple attentions in the mentalizing therapist. We close by discussing the importance of continued supervision in facilitating the maintaining of mentalizing glasses in therapy.